2019
DOI: 10.5194/hess-2019-80
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relevance and controls of preferential flow at the landscape scale

Abstract: Abstract. The spatial and temporal controls of preferential flow (PF) during infiltration are still not fully understood. Soil moisture sensor networks give the possibility to measure infiltration response in high temporal and spatial resolution. Therefore, we used a large-scale sensor network with 135 soil moisture profiles distributed across a complex catchment. The experimental design covers three major geological regions (Slate, Marl, Sandstone) and two land covers (forest, grassland) in Luxembourg. We ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…The observed differences were likely related to wetter conditions (e.g., less bypass flow due to hydrophobicity, larger hydraulic conductivity of the matrix) in the deforested part of the catchment (Figure 3) and the larger amount of direct rainfall (no interception). Whereas the results presented here showed clear differences in sequential flow occurrence, several earlier studies have reported clear differences in preferential flow occurrence that were related to different vegetation types [27,39,40,49]. Alaoui et al [27] found preferential flow both in forest and in grassland soil, but dye patterns suggested stronger interactions between macropores and matrix for forest soils.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationcontrasting
confidence: 69%
See 4 more Smart Citations
“…The observed differences were likely related to wetter conditions (e.g., less bypass flow due to hydrophobicity, larger hydraulic conductivity of the matrix) in the deforested part of the catchment (Figure 3) and the larger amount of direct rainfall (no interception). Whereas the results presented here showed clear differences in sequential flow occurrence, several earlier studies have reported clear differences in preferential flow occurrence that were related to different vegetation types [27,39,40,49]. Alaoui et al [27] found preferential flow both in forest and in grassland soil, but dye patterns suggested stronger interactions between macropores and matrix for forest soils.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationcontrasting
confidence: 69%
“…The macropores in the grassland soils, on the other hand, showed little interaction with the surroundings. Jin et al [39] and Demand et al [40] found clear differences in preferential flow occurrence between grassland and forested sites. Zhao et al [49] also observed more preferential flow occurrence for a forest site as compared to a grassland site.…”
Section: Analysis Of Differences In Sensor Response Due To Deforestationmentioning
confidence: 96%
See 3 more Smart Citations